PERSEPSI SISWA TERHADAP PELAKSANAAN PEMBELAJARAN BERBASIS E-LEARNING DI MADRASAH ALIYAH PONDOK PESANTREN DAR EL HIKMAH PEKANBARU - Wulan Anggraini; Sri Erlinda; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract : This research was conducted to determine the extent to which the implementation ofbased E-Learning-learning at Madrasah AliyahDar El Hikmah Islamic Boarding Scool Pekanbaru. Based on this background, the problem that arises is how the students' perceptions of the implementation ofbased e-learninglearning at Madrasah Aliyah Dar El Hikmah Islamic Boarding School Pekanbaru? The purpose of this study was to determine the perceptions of students of Madrasah Aliyah Islamic Boarding School Dar El Hikmah Pekanbaru on the implementation ofbased e-learninglearning. In this research the writer will present the datais the result of research conducted by the author at the research locationthat is done at Madrasah Aliyah Dar El Hikmah Islamic Boarding School Pekanbaru Jalan Manyar Sakti KM 12,5 Simpang Baru, Tampan, Pekanbaru, where this research usesobservation data collection techniques, interviews, and questionnaires. In this study, a population of 493 students, the authors took a sample of 15% of the total population. Thus the number of samples in this study were 74 students as respondents forfill out the author's research questionnaire. The results of this study were analyzed using quantitative descriptive analysis techniques. Quantitative descriptive analysis was carried out to get an overview of respondents' answers to the research variables used. Based on the results of the study, it was found that the average percentage value of the alternative dominant respondent's answers was 50,27% where this range was in the "Good" category with the presence in the range 50,01-75%. Thus the Student's Perception of the Implementation ofBased E-Learning-Learning at Madrasah Aliyah Dar El Hikmah Islamic Boarding School Pekanbaru is Good.Key Words: Perception, Students, Based E-Learning-Learning